2018
DOI: 10.2991/jrnal.2018.5.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Development of A Passively Powered Knee Exoskeleton for Squat Lifting

Abstract: This paper proposes a knee exoskeleton with passive-powering mechanism to provide power assistance to the knee joint during squat lifting of objects from the ground. It is designed to capture and store 20% of the biomechanical energy dissipated at the biological knee joint during decent phase and return the harnessed energy in the ascent phase in a squatting cycle. The effectiveness of the proposed system was verified by evaluating performance of key muscles of knee joint using surface electromyography (sEMG) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 6 publications
(22 reference statements)
0
17
0
Order By: Relevance
“…However, most wearable robots are not designed for this action. A passive one-DoF knee exoskeleton was developed by Ranaweera et al [10] to help humans lift loads from the squatted position. This device employed two helical elastic springs on each knee.…”
Section: Knee Exoskeletonmentioning
confidence: 99%
See 3 more Smart Citations
“…However, most wearable robots are not designed for this action. A passive one-DoF knee exoskeleton was developed by Ranaweera et al [10] to help humans lift loads from the squatted position. This device employed two helical elastic springs on each knee.…”
Section: Knee Exoskeletonmentioning
confidence: 99%
“…The flexion/extension ankle motions are controlled by a DC servomotor, while the inversion/eversion motions are controlled use a spring and damper mechanism. Three pneumatic synthetic muscles are used to simulate the human leg [24], (c) springs [10], (d) a DC motor and pulley [25], (e) double pulleys [26].…”
Section: Ankle Exoskeletonmentioning
confidence: 99%
See 2 more Smart Citations
“…Lerner et al (2017) showed a reduction in knee extensor moment in individuals with crouch gait due to Cerebral Palsy when using a knee exoskeleton. A passive knee exoskeleton mechanism has shown to reduce the peak root-mean-square averages of surface electromyography signals of the knee extensor muscles by 30%–40% during squatting (Ranaweera et al, 2018). A subjective evaluation of a passive leg support exoskeleton (“noonee”) showed that it reduced discomfort during a simulated assembly task (Luger et al, 2019).…”
Section: Introductionmentioning
confidence: 99%